Pengaruh Kepribadian Dan Lingkungan Kerja Terhadap Kualitas Kerja Pegawai Kelurahan Pekayon Jaya, Kec. Bekasi Selatan - Putri Aprilia Hikayatunni’mah; Tungga Buana Irfana; Supriyanto Supriyanto; Djuni Thamrin; Matdio Siahaan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of personality and work environment on the quality of work of employees in Pekayon Jaya Village, Kec. South Bekasi. This research uses quantitative research and uses primary and secondary data. Data collection was carried out using interview and questionnaire methods and used a saturated sample method because it was taken from all 55 employees in Pekayon Jaya District. To find out the research results, the data was processed using SPSS version 26 software. The data analysis techniques used in this research were validity tests, reliability tests and reliability tests. Classic hypothesis testing, linear regression testing, hypothesis testing and correlation coefficient. The results of the research show that personality has a positive influence on the quality of employee work by showing a calculated Tvalue of 4.321 > Ttable 2.008 and a sig value of 0.000 < 0.05, and for the work environment it has a positive influence by showing a calculated t value of 3.811 > 2.008 t with a sig value of 0.000 <0.05. Meanwhile, simultaneously or together, personality and work environment have a positive influence on the quality of work of employees in Pekayon Jaya District, South Bekasi, by displaying a table of calculated Fvalues > Ftable, namely 43.064 > 3.18 and has a significance value of 0.000 < 0.05. And in the coefficient of determination test, the Adjusted R Square results obtained were 62.4% which could be explained by personality, work environment and work quality variables, while the remaining 37,6% could be explained by other variables for reasons other than the variables in this study.